Harmonizing Openness in the Zhuangzi: A Critique of Respecting Diversity - Luyao Li; Paul J. D’Ambrosio (Religions)
In contemporary societies, increasing diversity is often accompanied by intensified conflicts across various public domains. While respecting differences is commonly proposed as a solution, this necessarily narrows the scope of shared values, which correspondingly decreases the chances of developing harmony. Indeed, harmony is frequently criticized for potentially requiring uniformity, which would undermine diversity. This article addresses this challenge by exploring philosophical and religious perspectives drawn from the Zhuangzi. Specifically, we find that a type of dynamic openness can be found in the Zhuangzi which shifts the focus away from embracing a more static “diversity”. Here, openness is understood as emphasizing interconnectedness, mutual influence, and collective transformation, offering a framework for resolving conflicts beyond mere respect for differences. In this article, we argue that one type of philosophical–religious perspective that can be derived from the Zhuangzi advocates for harmonizing openness—a process that achieves consensus while fully allowing for individual differences, rather than enforcing the type of uniformity found in many calls to respect diversity. This perspective offers valuable insights for the navigation of conflict in an increasingly pluralistic world and provides a critique of more popular contemporary approaches.